KOMUNIKASI TERBUKA MELANGGENGKAN KEUTUHAN DAN KEHARMONISAN KELUARGA - Enung Asmaya (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2007)
Having a family life is a basic need of every individual. This is aimed at reaching a harmonious family life, both in sufficiency or in insufficiency. To achieve this State, every individual need to be aware of having bright and positive thinking and also regardful with praying to God. One effort to achieve this State is by having open communication, not formalistic, familiar, and warm among family members and also with God, Allah swt. Open communication will bring a family to the successful and harmonious life.